Study on the Diversity and Seasonal Variation of Zooplankton in Mahendranath Pond Siwan Bihar - Manoj kumar pandey, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Study on the Diversity and Seasonal Variation of Zooplankton in Mahendranath Pond Siwan Bihar